Materials for printed boards and other interconnecting structures. Reinforced base materials clad and unclad. Non-halogenated epoxide non-woven/woven E-glass reinforced laminate sheets of thermal conductivity (1.5W/m K) and defined flammability (vertical burning test), copper-clad for lead-free assembly Part 2-46, (16th April 2018) - British Standards Institution,
No abstract available